Flexible catholyte@carbon nanotube film electrode for high-performance lithium sulfur battery. (March 2017) - Kim, Sunwha; Song, Hyeonjun; Jeong, Youngjin
Abstract: A lithium sulfur (Li-S) battery is attracting considerable attention as a next-generation, high-performing battery. In response to the great demand for lightweight, high-capacity batteries, persistent efforts have been made to solve Li-S battery problems such as polysulfide shuttling. In particular, it has become important to develop a flexible battery in portable electronics. In this study, a Li-S battery is made by a catholyte (Li2 S6 ) solution-impregnated carbon nanotube (CNT) film (catholyte@CNT film) with a conductive 3D network structure. The flexibility and electrochemical properties of the prepared Li-S battery are analyzed. The Li-S battery made of the catholyte@CNT film yields an initial discharge capacity of 975 mAh/g and is stable after charge/discharge of 500 cycles. The battery retains more than 95% of its initial capacity even after 1000 cycles of a limited depth of charge/discharge. A pouch cell battery is fabricated to evaluate performance under several bending tests. As a result, it is observed that the battery maintains good open circuit voltage (OCV) despite 1000 repeated deformation tests and exhibits a stable cycling performance both in the folded and unfolded states. These findings suggest that the CNT film is highly suitable for use as an electrode in flexible Li-S batteries. Graphical abstract: